Pengaruh Literasi Digital dan Status Sosial-Ekonomi terhadap Kemandirian Belajar Siswa: Studi Kasual Komparatif Penerapan Pembelajaran Face to Face E-Learning di Madrasah Aliyah - Zetri Rahmat; Retno Widianti; Ina Lestari (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2023)
This study aims to determine digital literacy and economic status on student learning independence and to determine differences in student learning independence between online and offline. This study uses a quantitative approach with a comparative causal method. The population in this study were MA students in Pekanbaru City with a sample of 379 students. The sampling method used stratified random sampling with the technique of determining the number of samples using the Isaac and Michael formula. The instrument in the study used a questionnaire. Based on the regression test for the influence of socio-economic and digital literacy on independence, the results obtained H0 < 0,05 so H1, which means that there is a significant influence between socio-economic and digital literacy on student independence. In the socio-economic correlation and digital literacy on student learning independence, it is obtained H0 > 0,05 which means there is no socio-economic influence on student learning independence and the results are H0 < 0,05 which means there is a significant influence on student learning independence. Based on the results of the Mann-Whitney obtained that H0 was accepted, which means there was no significant difference between student independence with online and face to face. The difference in students digital literacy abilities between online test Mann-Whitney results of  H0 rejected, which means that there is a significant difference in students' digital literacy abilities between online and face to face.